A Particular Medullary-Spinal Inhibitory Pathway is Recruited for the Expression of Muscle Atonia During REM Sleep. (November 2018) - Valencia Garcia, Sara; Luppi, Pierre-Hervé; Fort, Patrice
Muscle atonia is a major pathognomonic sign of paradoxical sleep (PS; coined REM Sleep), during which dreams mainly occur. In the 1980s, an idiopathic syndrome called REM sleep behavior disorder (RBD) was described in patients endowed with loss of PS paralysis concomitant to abnormal movements, suggesting a dysfunction of PS networks. Another major clinical RBD feature is its prevalent phenoconversion into synucleinopathies as Parkinson's disease in a delay of 10-15 years after diagnosis. Thus, we undertook experiments in rats to disentangle brainstem networks involved in PS, including atonia. We first identified a contingent of pontine glutamate neurons recruited during PS with inputs to the ventromedial medulla (vmM) where they contact γ-aminobutyric acid (GABA)/glycine inhibitory neurons also activated during PS. Here, we further show that these vmM inhibitory neurons send efferents to somatic spinal motoneurons until lumbar levels. As reported for the pontine generator, the genetic inactivation of the vmM inhibitory neurons abolishes atonia during PS without effects on waking locomotion and is sufficient to recapitulate major RBD symptoms. These original data suggest that RBD may reflect a severe dysfunction and/or degeneration linked to a developing synucleinopathic attack targeting specifically neurons that generate PS-specific atonia.